Brand trust and avoidance following brand crisis: A quasi-experiment on the effect of franchisor statements. Issue 5 (September 2016) - Shin, Hyunju; Casidy, Riza; Yoon, Alyssa; Yoon, So-Hyang
Abstract Although franchising has become an important growth strategy in several industries over the last few decades, there are few empirical studies about the effects of franchisor communication strategy on customer responses in the context of franchise brand crisis. Two quasi-experimental studies were conducted to test the effect of a franchisor ownership separation statement on brand trust and brand avoidance following a brand crisis situation. Results show that a franchisor's explicit communication of the franchise brand's individual ownership business structure is useful in preventing further negative spillover effect throughout the franchised chain when the brand crisis occurs at a single franchise location. The authors also investigate the mechanism through which such communication influences customer behavior and the moderating effect of the brand crisis severity in affecting brand evaluation. These results offer guidance to franchise brand managers by providing insight into how to overcome a franchise brand crisis and by suggesting franchise context-specific managerial recommendations.